Gastropleural fistula following pulmonary resection. - O'Keefe, P. A. (1993)
A 77 year old man with an eight month history of polymyalgia rheumatica treated by steroids underwent left lower lobectomy for a non-small cell carcinoma. Following discharge he developed a pneumothorax, empyema, septicaemia, and acute renal failure. Reinvestigation and reoperation showed this to be caused by a non-malignant non-traumatic direct gastropleural fistula.